GAMBARAN KECEMASAN PRIMIPARA DALAM PERAWATAN BAYI BARU LAHIR DI PUSKESMAS SUKOREJO - Siti Aisah; Fitria Jannatul Laili (LPPM Universitas dr. Soebandi, 2015)
Anxiety is to gridlock that was not clear and spread, which relate to feeling not certain and not helpless. Many women’s health is worried about her beby, feeling uneasy and guilty that she feels after giving birth to her first child because her own more attention to her beby. To take care of beby was not a difficult but often mother Primipara have concern in fostering baby. According to data collection that will be done at the end of 2012 in the community health center sukorejo Bangsalsari obtained 840 mother giving birth, consisting of 420 mother multipara and mother primipara. In The month of October survey in 2013 mother were obtained from 18 primipara that gave birt to take care of her beby, in both bathe, treat umbilical cord and giving water mother’s milk less true. The aim of the research is to know the picture high anxiety mothers primipara in the care newly born baby in the community Health Center Sukorejo sub-district Bangsalsari Jember Regency. This research is Descritive. The population in this research is mother primipara 1-7 days post in october the mothers 18 primipara. Loding technique a sample total product sampling as many as 18 mother her purifying primipara. Data collection using quistionnaries. Results of research most respondents age of 20-25 of 45 percent, from the factors education most respondents educated junior high school that is 56 percent, and a half- rsondens who does not work ( IRT 50 percent. Most mother 78 percent primipara, anxiety at the time to treat newborn baby. Therefore expected to health workers particularly midwives to improve service obstetric patients at the time that pregnant mother in the gave birth periodid not experience anxiety in fostering newly born baby.